Urban farmers coping strategies in the wake of urbanization and changing market in Tamale, Northern Ghana - Nchanji, Eileen Bogweh; Nchanji Yvonne Kiki (Elsevier, 2022)
Vegetable cultivation is a survival strategy for the urban population, especially with the increasing population, urbanization, and high unemployment rate. For decades, men have practiced vegetable cultivation in Tamale's metropolitan city, with women being involved at the last node of the value chain – marketing. Women are known as market queens, and culturally, sell foodstuff in the market, unlike men who can’t do the same. These market queens buy vegetables from farm gates and sell them at wholesale prices to other market women who retail them in the market. An ethnographic study was carried out to understand how farmers carry out their farming activities and marketing in the face of changing market trends and urbanization and how urbanization and markets shape and regulate farmers’ agricultural practices with implications for urban agricultural policy and town planning. Results show that urbanization has influenced urban and peri-urban land prices resulting in the leasing of prime agricultural lands by chiefs for industrial and residential purposes. As such, farmers cope by negotiating farmland with government and private institutions, with more success. Farmers also practice mixed cropping to buffer climatic shocks and address market gluts to meet household needs and income. Even though urbanization poses a risk for farmers, it also creates spaces where farmers’ practices are reshaped as they network with agro-dealers, buyers, and researchers in their everyday activities, contributing to urban gardening policies and Sustainable Development Goal (SDG) 11